Direct Multicomponent Synthesis of C3-Arylated Pyrroles under Catalyst-Free Conditions - Pawar, Amol Prakash; Jangir, Reena; Dolas, Atul Jankiram; Nagare, Yadav Kacharu; Rangan, Krishnan; Iype, Eldhose; Kumar, Indresh (Synthesis, 2024)
An operationally simple catalyst-free protocol for the direct regiospecific synthesis of C3-arylated/alkenylated pyrroles has been developed. The enamine-intermediate, in situ generated from succinaldehyde and a primary amine, was trapped with activated carbonyls before the Paal–Knorr reaction in a direct multicomponent ‘just-mix’ protocol to furnish pyrroles in good yields. Several C3-substituted N-alkylpyrroles have been prepared under open-flask conditions, avoiding protection-deprotection chemistry.
Keywords: pyrrole; quinone; enamine; Paal–Knorr reaction; one-pot